Pengaruh Price (Harga) dan Product (Produk) Terhadap Minat Pembelian Event Package di Perusahaan Lokacipta Arta Dutasindo - Asmarani, I Gusti Ayu Ratih; Asmarani, Luh Putu; Putra, I Putu Gd Aditya Pradnya (Journal of Event and Convention Management, 2023)
This study is to determine the effect of Price and Product on interest in purchasing event packages at the Lokacipta Arta Dutasindo Company. The number of research samples was as many as 97 respondents using a saturated sample. Data collection is done by distributing questionnaires to all clients who have purchased or have used products. The data analysis technique used is descriptive quantitative through a statistical approach using a significant questionnaire and analyzed by multiple linear regression, classical assumption test of regression, individual parameter significance (t-test), simultaneous test (F test), and coefficient of determination R². The results of this study show that the adjusted values of R2 are 0.691, meaning 69.1% changes in Purchase Interest which are influenced by Price with 34.1% results and Product with 46.4% results, while the remaining 31, 9% is influenced by other factors outside this research. The results showed that there was a significant effect of Price and Product partially on purchase intention. Simultaneously, it is also seen that there is a significant influence of Price and Product on purchase intention.